The gamma-glutamyl transpeptidase to platelet ratio: a good noninvasive biomarker for predicting for the occurrence and prognosis of patients with hepatitis E virus-related acute liver failure - Shuai Zhu; Jun Yuan; Feng Ju; Mengmeng Gu; Ze Xiang; Yan Zhang (Frontiers in Medicine)
BackgroundThe relationship between GPR and hepatitis E has not been reported. This study evaluates the GPR levels in AHE patients and HEV-ALF patients and explores the role of GPR levels in the prognosis of HEV-ALF patients, offering new strategies and methods for the diagnosis and prognosis of HEV-ALF patients.MethodsSerum samples were collected from 206 AHE patients and 217 HEV-ALF patients admitted to the First Affiliated Hospital of Zhejiang University School of Medicine, Suzhou Yongding Hospital, and Nanjing Medical University Affiliated Suzhou Hospital between January 1, 2017, and November 30, 2024.ResultsThe GPR level in the HEV-ALF group was significantly higher than in the AHE group (p < 0.001). OPLS-DA analysis revealed that INR, TBIL, PLT, GPR, TCH, ALT, AFP, TP, ALB, and AST were the major influential factors for the occurrence of HEV-ALF. GPR showed good diagnostic performance with an AUC of 0.701. DCA further supported the utility of GPR across a range of threshold probabilities. Regarding the prediction of 30-day mortality, GPR levels were significantly higher in the non-survival group compared to the survival group (p < 0.001). OPLS-DA analysis highlighted GPR as the most influential factor for predicting 30-day mortality. GPR demonstrated an AUC of 0.703. DCA results also indicated GPR’s strong decision-making ability for predicting 30-day mortality in HEV-ALF patients.ConclusionGPR is highly expressed in HEV-ALF patients and is closely related to their prognosis.